2021
DOI: 10.1126/science.abg2009
|View full text |Cite
|
Sign up to set email alerts
|

Neural representations of space in the hippocampus of a food-caching bird

Abstract: Spatial memory in vertebrates requires brain regions homologous to the mammalian hippocampus. Between vertebrate clades, however, these regions are anatomically distinct and appear to produce different spatial patterns of neural activity. We asked whether hippocampal activity is fundamentally different even between distant vertebrates that share a strong dependence on spatial memory. We studied tufted titmice, food-caching birds capable of remembering many concealed food locations. We found mammalian-like neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
119
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 68 publications
(80 reference statements)
7
119
1
Order By: Relevance
“…To best of our knowledge, so far only two other studies investigated the involvement of the avian hippocampus in the exploration of novel environments (Mayer et al, 2018;Morandi-Raikova and Mayer, 2020). Altogether, these studies contribute to the vast literature showing that, despite the fundamental differences in the structure of the hippocampal formation in birds and mammals (Striedter, 2016), its involvement in spatial 14 functions is shared among the two clades (Bingman et al, 2005;Siegel et al, 2005;Hough and Bingman, 2008;Kahn and Bingman, 2009;Mayer et al, 2010Mayer et al, , 2013Mayer et al, , 2016Mayer and Bischof, 2013;Coppola et al, 2015Coppola et al, , 2016Sherry et al, 2017;Lormat et al, 2020;Morandi-Raikova and Mayer, 2021;Payne et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…To best of our knowledge, so far only two other studies investigated the involvement of the avian hippocampus in the exploration of novel environments (Mayer et al, 2018;Morandi-Raikova and Mayer, 2020). Altogether, these studies contribute to the vast literature showing that, despite the fundamental differences in the structure of the hippocampal formation in birds and mammals (Striedter, 2016), its involvement in spatial 14 functions is shared among the two clades (Bingman et al, 2005;Siegel et al, 2005;Hough and Bingman, 2008;Kahn and Bingman, 2009;Mayer et al, 2010Mayer et al, , 2013Mayer et al, , 2016Mayer and Bischof, 2013;Coppola et al, 2015Coppola et al, , 2016Sherry et al, 2017;Lormat et al, 2020;Morandi-Raikova and Mayer, 2021;Payne et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…The more locations are visited the higher number of hippocampal cells should express c-Fos. Moreover, based on previous studies carried out in other bird species, one can expect to find a higher degree of activation in the anterior segment of Hp during spatial mapping (Payne et al, 2021). However, no study so far reported differences in activation between the anterior, intermediate, and posterior hippocampal segments in domestic chicks.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations